Use of MAG1 Recombinant Antigen for Diagnosis of Toxoplasma gondii Infection in Humans - Holec, Lucyna (American Society for Microbiology, 2007)
This paper describes the cloning, purification, and serological applications of matrix antigen MAG1 of Toxoplasma gondii. The expression system used allows the production of a large amount of T. gondii recombinant protein, which was assessed for its potential use in an enzyme-linked immunosorbent assay (ELISA) for detection of T. gondii infection in humans. Serum samples from 117 patients with different stages of infection, along with 10 serum samples from seronegative patients obtained for routine diagnostic tests, were used. The results were compared with those of an ELISA that uses a native T. gondii antigen extract. The MAG1 antigen detected antibodies more frequently from the acute stage (97.3%) than from the chronic stage (7.5%) of toxoplasmosis. Hence, this antigen may be used as a tool for detection of T. gondii immunoglobulin G antibodies in persons with acute toxoplasmosis.